2011
DOI: 10.1007/s00540-011-1108-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognition preceding cardiac surgery is related to cerebral ischemic lesions

Abstract: These findings suggest that preoperative cognitive impairment associated with cerebral ischemic lesions and an increased risk of postoperative cognitive dysfunction existed in our patient cohort undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Lund et al [37] evaluated patients who had undergone an on-pump coronary artery bypass surgery and found that the severity of presurgical white matter abnormalities, a brain MRI variable associated with ischemia and small vessel vascular disease, predicted the frequency of postoperative cognitive impairment at 3 months postsurgery. Maekawa et al [38 • ] found that white matter lesions and cerebral infarctions on MRI scans were predictive of impaired cognition prior to elective cardiac surgery and placed these patients at a higher risk for postoperative neurological dysfunction. Similarly, preoperative white matter fractional anisotropy acquired via magnetic resonance diffusion methods has been associated with postoperative delirium [39 • ].…”
Section: Potential Mechanisms For Postoperative Cognitive Disordersmentioning
confidence: 99%
“…Lund et al [37] evaluated patients who had undergone an on-pump coronary artery bypass surgery and found that the severity of presurgical white matter abnormalities, a brain MRI variable associated with ischemia and small vessel vascular disease, predicted the frequency of postoperative cognitive impairment at 3 months postsurgery. Maekawa et al [38 • ] found that white matter lesions and cerebral infarctions on MRI scans were predictive of impaired cognition prior to elective cardiac surgery and placed these patients at a higher risk for postoperative neurological dysfunction. Similarly, preoperative white matter fractional anisotropy acquired via magnetic resonance diffusion methods has been associated with postoperative delirium [39 • ].…”
Section: Potential Mechanisms For Postoperative Cognitive Disordersmentioning
confidence: 99%
“…Factors negatively related to the condition of blood vessels, including those of the brain, such as advanced age, preexisting (cerebro)vascular disease, and the presence of (cerebro) vascular risk factors, play an important role in the pathogenesis of cognitive dysfunction after cardiac surgery. In fact, preoperative small ischaemic lesions and cognitive impairment have been reported in a considerable proportion of candidates for cardiac surgery and have been shown to be predictors of both early and late postoperative cognitive dysfunction [11,12]. It has been suggested that the apolipoprotein E (APOE) ε4 allele, a genetic risk factor for both atherosclerosis and Alzheimer's disease, plays an explanatory role.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…5,6 To determine whether the patient had POCD, we compared groups using an absolute score (MMSEand MoCA-specific score), which is more practical in the clinical setting than relative methods used in previous studies (previous literature had used decrease in 0.5-1.0 SD or 20% of score as significant. 7 ) Both MMSE and MoCA tests were chosen because of their relative ease to perform, while including most of the important domains of cognitive function (orientation, memory, calculation, attention, abstraction, and executive function).…”
Section: Resultsmentioning
confidence: 99%